The «First Time Instance» as Regards Restitution of Removed Cultural Properties - Scovazzi, Tulio (2012)
A rule of customary international law is commonly believed to consist in «a general practice accepted as law», as stated in Art. 38, para. 1, b, of the Statute of the International Court of Justice. In studying the process that leads to the creation of a new customary rule where no rule existed or the replacement of an old rule by a new one, particularly important is the «first time» instance, that is the case when the need for a new regime is publicly manifested for the first time. As such a need cannot be grounded on legal precedents, for the simple reason that they do not exist, reasons of moral, political, social, economic or cultural character are often put forward to explain the innovation and make it acceptable for other States.